Liver Transplants for Alcoholic Liver Disease - RJ Fingerote; VG Bain; RN Fedorak (Canadian Journal of Gastroenterology)
Alcohol related end-stage liver disease is a principal cause of liver failure. The scarcity of donor livers and the predominance of alcohol related end-stage liver disease has raised the issue of including alcoholics as candidates for liver transplantation. In rationalizing the arguments for and against the treatment of alcoholic end-stage liver disease with transplantation, factors such as recidivism, resource allocation and principles of medical practice must be considered. Public confidence in organ transplantation depends on the scientific validity and moral integrity of the policies adopted. Sound policies will prove defensible while policies based on perceptions or prejudices will, in the long run, harm the process.